Analysis of Palm Oil Industry Liquid Waste Management at PT. Citra Putra Kebun Asri in South Kalimantan Province - Surya Eka Putra; Eri Barlian; Nurhasan Syah; Iswandi Umar; Indang Dewata (Jurnal Penelitian Pendidikan IPA, 2023)
Oil palm plantations are currently experiencing quite rapid growth; this has resulted in a large number of oil palm fruit processing industriespalm oil (crude palm oil) and palm kernel (palm kernel). The more oil palm fruit that is processed, the more liquid waste it produces. Liquid waste generated during the production process can harm the environment because of the high organic matter contained therein. The purpose of this study was to analyze the management of palm oil industrial wastewater at PT Citra Putra Kebun Asri.The method used in this study is an exploratory method and the collection and testing of data is done by graph sampling. The results of the analysis contained in the palm oil industrial wastewater, namely the pH content ranges from 4-8.5. The content of BOD and COD in the first pool had quite high levels, this was due to (human error) during testing, factory measuring instruments that had not been calibrated and inaccurate sampling by factory staff. While the BOD and COD in the application pond have values ​​that are in accordance with the liquid waste quality standards with BOD values ​​below 100 mh/L and COD values ​​below 250 mg/L